Antioxidant, antihyperglycemic, and antidyslipidemic effects of Brazilian-native fruit extracts in an animal model of insulin resistance - Juliane de Souza Cardoso; Pathise Souto Oliveira; Natália Pontes Bona; Flávia Aleixo Vasconcellos; Jucimara Baldissarelli; Marcia Vizzotto; Mayara Sandrielly Pereira Soares; Vanessa Plasse Ramos; Roselia Maria Spanevello; Claiton Leoneti Lencina; Rejane Giacomelli Tavares; Francieli Moro Stefanello (Taylor & Francis Group, 2018)
Objective: Insulin resistance (IR) plays an important role in the development of many diseases, such as diabetes mellitus. Therefore, the aim of the present study was to evaluate the effects of the extracts from fruits native to Brazil on metabolic parameters and hepatic oxidative markers in an animal model of insulin resistance induced by dexamethasone (DEX). Methods: Wistar rats received water or extracts of Eugenia uniflora or Psidium cattleianum, once a day for 21 days. For the last 5 days, the rats received an intraperitoneal injection of saline or DEX. Results: DEX caused a reduction in body weight gain and relative pancreatic weight, as well as glucose intolerance, and an increase in serum glucose and triacylglycerol levels. The extracts were found to prevent hyperglycemia and hypertriglyceridemia. DEX caused an increase in the levels of thiobarbituric acid-reactive substances and reactive oxygen species production in the liver of rats, and both extracts prevented these changes. In addition, hepatic glutathione peroxidase activity was reduced by DEX. However, total thiol content and activities of catalase, superoxide dismutase, and delta-aminolevulinate dehydratase were not altered in any of the tested groups. Conclusion: Fruit extracts of E. uniflora and P. cattleianum exhibited considerable antihyperglycemic, antidyslipidemic, and antioxidant effects, and may be useful in the therapeutic management of alterations due to IR.